Physical activity enhances fecal lactobacilli in rats chronically drinking sweetened cola beverage - Marusakova Margareta; Dudik Boris; Hadova Katarina; Kmecova Zuzana; Kralova Eva; Krenek Peter; Bilkova Andrea; Klimas Jan (Open Life Sciences, 2022)
Overweight and obesity have been linked with increased intake of sugar-sweetened beverages. On the other hand, physical activity has been known to lead to weight loss. Therefore, we hypothesized that exercise might influence the Lactobacillus population in fecal microbiota as their changed abundance is often associated with shifts in the physical activity and diet. In our experiment, Wistar rats were allocated into groups with normal feed or added sugar-sweetened beverages with or without access to a running wheel. Interestingly, only a combination of physical activity and sweetened beverage intake was associated with a significant increase in fecal lactobacilli abundance, suggesting a connection between exercise and a rise in lactobacilli abundance. Moreover, physical activity has improved weight-related parameters and led to increased plasma and mRNA adiponectin levels. Ghrelin and leptin plasma levels were unaltered. Taken together, our results demonstrate that effect of physical activity on adiposity even during unhealthy feeding patterns is accompanied by increased lactobacilli abundance in the fecal microbiota population.